Profesi Auditor Internal Masa Mendatang - Budianto Tedjasuksmana (BIP's JURNAL BISNIS PERSPEKTIF, 2011)
Internal Audit faces new challenges in today's business environmentShareholders are demanding growth, regulators are expanding their scope of scrutiny, and new markets are constantly developing and evolving. To add value during rapidly changing times, internal audit needs more than ever to understand its role, prioritize its efforts,, and operate from its core strengths.